2008
DOI: 10.3349/ymj.2008.49.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Role of Brain Inflammation in Epileptogenesis

Abstract: Inflammation is known to participate in the mediation of a growing number of acute and chronic neurological disorders. Even so, the involvement of inflammation in the pathogenesis of epilepsy and seizure-induced brain damage has only recently been appreciated. Inflammatory processes, including activation of microglia and astrocytes and production of proinflammatory cytokines and related molecules, have been described in human epilepsy patients as well as in experimental models of epilepsy. For many decades, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
2
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(138 citation statements)
references
References 147 publications
5
124
2
7
Order By: Relevance
“…However, the role of inflammatory responses in the pathogenesis of epilepsy and seizure-induced brain damage has been appreciated only recently. Inflammatory processes, including activation of microglia and astrocytes and production of proinflammatory cytokines such as TNF-α, IL-1β, IL-6, and related molecules, have been described in human epilepsy patients as well as in experimental models of epilepsy (Vezzani & Granata, 2005;Choi & Koh, 2008). TNF-α, IL-1β, and IL-1ra are highly inducible under different forms of stress, such as excitatory neurotransmitter excess occurring during seizures, in infection and inflammation, and during neurotrauma (Bartfai et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of inflammatory responses in the pathogenesis of epilepsy and seizure-induced brain damage has been appreciated only recently. Inflammatory processes, including activation of microglia and astrocytes and production of proinflammatory cytokines such as TNF-α, IL-1β, IL-6, and related molecules, have been described in human epilepsy patients as well as in experimental models of epilepsy (Vezzani & Granata, 2005;Choi & Koh, 2008). TNF-α, IL-1β, and IL-1ra are highly inducible under different forms of stress, such as excitatory neurotransmitter excess occurring during seizures, in infection and inflammation, and during neurotrauma (Bartfai et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…There is also compelling evidence that inflammatory cytokines or immune reactions after brain injury have an important role in neuronal excitability and epileptogenesis (Choi and Koh, 2008;Fabene et al, 2008;Vezzani et al, 2008a). Studies have shown that soon after an acute brain injury, activated microglia and astrocytes provide a rich source of cytokines such as interleukin (IL)-6, IL-1b, and tumor necrosis factor a (Choi and Koh, 2008;Ridet et al, 1997;Rizzi et al, 2003;Viviani et al, 2003), which promote neuronal excitability by modulating extracellular glutamate levels Vezzani et al, 2008b). IL-1b was reported to be responsible for increasing N-methyl-D-aspartate receptor-mediated Ca 2 + influx and surface expression of AMPA receptor by binding to the AMPA receptor IL-1RI, which colocalizes with N-methyl-D-aspartate receptors (Viviani et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, growing evidence has demonstrated that immune system dysfunction and inflammatory signaling may play an instrumental role in all the phases of the epilepsy development [14-16]. Modulation of immunity and inflammatory response exerted remarkable protective effects on the epilepsy brain in experimental animal studies [17, 18]. Meanwhile, auto-antibodies were detected in the DRE patients and immunotherapy has been shown to benefit these patients [19].…”
Section: Introductionmentioning
confidence: 99%